2019
DOI: 10.1038/s41586-019-1018-5
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule ion channels increase host defences in cystic fibrosis airway epithelia

Abstract: Loss-of-function mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) compromise epithelial HCO 3 − and Cl − secretion, reduce airway surface liquid (ASL) pH, and impair respiratory host defenses in people with cystic fibrosis (CF) 1 – 3 . Here we report that apical addition of an unselective ion channel-forming small molecule, amphotericin B (AmB), restored HCO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 60 publications
2
92
0
2
Order By: Relevance
“…In contrast, G85E, which is located in the same transmembrane span 1 (TM1) as E92K, shows no residual PM CFTR and minimal rescue by any CFTR modulators to date (Figures 1-5; [31,32]). It is clear that this mutation seems refractory to any available CFTR modulator drug, underscoring the need for alternative treatments for these patients, such as mutation-agnostic gene/mRNA therapies, modulation of alternative ion channels or small molecule induced ion channel strategies [16,[33][34][35][36]. A455E is associated with milder CF than the other rare CFTR mutations studied and has multiple proposed defects, ranging from less protein (class V), to impaired processing (class II) and conductance (class IV) [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, G85E, which is located in the same transmembrane span 1 (TM1) as E92K, shows no residual PM CFTR and minimal rescue by any CFTR modulators to date (Figures 1-5; [31,32]). It is clear that this mutation seems refractory to any available CFTR modulator drug, underscoring the need for alternative treatments for these patients, such as mutation-agnostic gene/mRNA therapies, modulation of alternative ion channels or small molecule induced ion channel strategies [16,[33][34][35][36]. A455E is associated with milder CF than the other rare CFTR mutations studied and has multiple proposed defects, ranging from less protein (class V), to impaired processing (class II) and conductance (class IV) [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[7] This nonselective channel was shown to restore the ability of lung cells to secrete HCO 3 À ,t hus enhancing the antibiotic activity of the airway surfacel iquid and reducing its viscosity. [7] The development of small drug-like molecules capable of mediatings elective transmembrane anion transport remains imperative, and is af ield of intensiver esearch. [8] Most of these molecules have been designed by applying knowledge acquired through the development of anion receptors, [9] couplingn atural [10] or synthetic platforms with suitable binding units that operate through conventional or unconventional hydrogen bonds, [11] involving halogen-, [12] chalcogen-, [13] or pnictogen-bonding interactions, [13c] or even through anion-p interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The ortho-phenylene scaffold was selected due to its chemical versatility allied with its successful use in the development of anion transporters. [21] Thet hiophene or benzo[b]thiophene moieties were directly linked to the central ortho-phenylene core via their C a or C b carbon atoms, leading to the substitution isomers a (3,4,8,9)a nd b (6,7,14,15), akin to assembling Lego bricks. Moreover,t he benzo[b]thiophene moiety Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in pigs with deleted cystic fibrosis transmembrane receptor (CFTR) have shown that an aerosol treatment with amphotericin B, a toxic antifungal agent, formulated in liposomes with cholesterol, restored airway pH levels. The authors suggest that similar aerosol treatment would help CF patients with many different CFTR mutations . Similarly, inhalation may also improve the ability of type‐1 interferon to treat Epstein‐Barr virus .…”
Section: Finding New Uses For Approved Drugsmentioning
confidence: 99%